Data-driven Management and Taylorist Fantasies: A Case Study of Performance Quantification in the Indian IT Services Industry - Chakramakkil Sathian, Thomson (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2024)
Human capital management (HCM) software applications are being widely used to assess the performance of knowledge workers in various sectors of the Indian economy. The use of data-driven performance management systems is claimed to make the performance appraisals fairer and more transparent to the worker, and their supposed objectivity is used to justify their deployment in the workplace as instruments of remote surveillance. This paper presents insights from the case study of a performance management system that was installed at an Indian IT services organisation following the transition to remote work. Despite its mobilisation around greater accuracy and objectivity in performance appraisals, the paper demonstrates that techniques of quantification in the system generated information that was empty of any managerial value. The dichotomous understanding of productivity encoded in the system also entrenched the subjective interests of managers into performance appraisals, creating conflicts of interest in supervision that eroded the interests of the workers. As the system misread and distorted the everyday realities of work, the workers governed by it were compelled to engage in “meta work” (Maggiori 2023) that effectively undermined their productivity. By staging the empirical insights from this case study within the politically fraught character of digital Taylorism, the paper seeks to understand why the performance management system failed to meet the sanguine promises of the digital that are often marshalled around data-driven management. Based on evidence from the Indian IT sector, it argues that the translation of worker activities into egregiously oversimplified productivity data, and the eventual normalization of the data using statistical techniques, enabled the organisation to translate the worker population into a fleet of disposable human capital. This, it further argues, has been a strategy that has been in place not only to control alienated labour but also to protect the IT industry’s ability to arbitrage labour costs amidst the vagaries of informational capitalism.